Tìm x
1) \(\left(\dfrac{1}{16}\right)^x=\left(\dfrac{1}{8}\right)^6\) 2) \(\left(\dfrac{1}{16}\right)^x=\left(\dfrac{1}{8}\right)^{36}\) 3) \(\left(\dfrac{1}{81}\right)^x=\left(\dfrac{1}{27}\right)^4\)
4) \(\left(\dfrac{4}{9}\right)^x=\left(\dfrac{8}{27}\right)^{10}\) 5) \(2^x=4^5.4^3\) help me !!!!
Tính
a, A = \(\dfrac{16^3.3^{10}+120.6^9}{4^6.3^{12}+6^{11}}\)
b, B = \(\left(\dfrac{3}{7}.\dfrac{4}{15}+\dfrac{1}{3}.9^{15}\right).\dfrac{1}{3}.\dfrac{6^8}{12^4}\)
c, C = \(\dfrac{10^4.81-16.15^2}{4^4.675}\)
Cho 2 biểu thức D và E như sau
\(D=\dfrac{10}{56}+\dfrac{10}{140}+\dfrac{10}{260}+...+\dfrac{10}{1400}\)
\(E=\dfrac{1}{1+2}+\dfrac{1}{1+2+3}+\dfrac{1}{1+2+3+4}+...+\dfrac{1}{1+2+3+4+...+24}\)
Tính \(\dfrac{D}{E}\)
tìm x :
a) \(\dfrac{x+1}{7}+\dfrac{x+1}{8}=\dfrac{x+1}{9}+\dfrac{x+1}{10}\)
b) \(\dfrac{x+1}{12}+\dfrac{x^2}{11}=\dfrac{x+3}{10}+\dfrac{x+4}{9}\)
c) \(\dfrac{x-2}{x-1}=\dfrac{x+4}{x+7}\)
d)\(\dfrac{3x+2}{5x+7}=\dfrac{3x-1}{5x-3}\)
2 tìm x,y,z
a) \(\dfrac{x}{2}=\dfrac{y}{3},\dfrac{y}{4}=\dfrac{z}{5}vàx^2-y^2=-16\)
b)2x=3y,5x=7z và 3x-7y+5z=30
\(A=\left(2\dfrac{1}{3}+3\dfrac{1}{2}\right):\left(-4\dfrac{1}{6}+3\dfrac{1}{7}\right)+7\dfrac{1}{2}\)
\(B=4\dfrac{25}{16}+25\cdot\left(\dfrac{9}{16}:\dfrac{125}{64}\right):\left(-\dfrac{27}{8}\right)\)
giải hộ mk nhanh nhanh nhoa ☺
1. Tìm tỉ số \(\dfrac{x}{y}\) biết \(\dfrac{2x-y}{x+y}\)=\(\dfrac{2}{3}\)
2. Tìm x:
a) 3,8 : (2x) = \(\dfrac{1}{4}:2\dfrac{2}{3}\)
b) \(1\dfrac{1}{3}\) : 0,8 = \(\dfrac{2}{3}\) : (0,1x)
c) \(\dfrac{x}{-15}\) = \(\dfrac{-60}{x}\)
d) \(\dfrac{-2}{x}=\dfrac{-x}{\dfrac{8}{25}}\)
e) 0,2 : \(1\dfrac{1}{5}\)= \(\dfrac{2}{3}\) : (6x+7)
3. Tính A = \(\dfrac{8^{10}+4^{10}}{8^4+4^{11}}\)
Câu 1)
1) \(\dfrac{11}{24}\)−\(\dfrac{5}{41}\)+\(\dfrac{13}{24}\)+0,5−\(\dfrac{36}{41}\)=
2)12÷\(\left(\dfrac{3}{4}-\dfrac{5}{6}\right)^2\)=
3) (\(1+\dfrac{2}{3}-\dfrac{1}{4}\))\(\left(0,8-\dfrac{3}{4}\right)^2\) =
4)\(16\dfrac{2}{7}\)÷(\(\dfrac{-3}{5}\))+\(28\dfrac{2}{7}\)÷\(\dfrac{3}{5}\)
5)\(\left(2^2\div\dfrac{4}{3}-\dfrac{1}{2}\right)\times\dfrac{6}{5}-17\)
6)\(\left(\dfrac{1}{3}\right)^{50}\times\left(-9\right)^{25}-\dfrac{2}{3}\div4\)
Tính
a) \(\dfrac{-2}{3}+\dfrac{3}{4}-\dfrac{-1}{6}+\dfrac{-2}{5}\)
b) \(\dfrac{-2}{3}+\dfrac{-1}{5}+\dfrac{3}{4}-\dfrac{5}{6}-\dfrac{-7}{10}\)
b) -x - 2 = \(\dfrac{5}{4}\) c) \(\dfrac{4}{3}-\left(x-\dfrac{1}{5}\right)=\left|\dfrac{-3}{10}+\dfrac{1}{2}\right|-\dfrac{1}{6}\) d) \(\dfrac{1}{3}-\left(\dfrac{2}{3}-x+\dfrac{5}{4}\right)=\dfrac{7}{12}-\left(\dfrac{5}{2}-\dfrac{13}{6}\right)\)